A silicone flexible strain sensing fiber and a method of making the same

CN122879852APending Publication Date: 2026-10-09SUZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611393560.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

而目前已报道的有机硅纤维其直径都在500微米以上甚至达毫米级别,这直接导致纤维的弯曲刚度和扭转刚度显著增加,柔韧性欠佳,使其难以承受加捻、打结、编织等纺织加工过程中的高曲率形变,为未来通过加捻、织造等工艺将其无缝集成于智能服装中带来了严峻挑战

Benefits of technology

本发明所述有机硅柔性应变传感细纤维的制备方法,将细颗粒碳基填料碳黑和多壁碳纳米管混入有机硅流体中,降低有机硅复合纺丝液的弹性,避免了纺丝液在喷丝口膨胀,碳基材料填充还可以改善基体导热能力,从而可促进纺丝过程中纺丝液更快速和均匀低固化、交联,这也在一定程度上避免纺丝体出口膨胀,从而在不降低传感水平的基础上得到细纤维;通过采用高纺丝温度可使有机硅纺丝液在喷丝口位置快速固化交联从而抑制流体在喷丝口膨胀,通过减小纺丝材料出口弹性防止纤维变粗,从而得到可控直径的有机硅细纤维,更适合后端织造工艺和设备。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879852A_ABST
    Figure CN122879852A_ABST
Patent Text Reader

Abstract

The application discloses a kind of organic silicon flexible strain sensing fine fibers and preparation method thereof, method includes: carbon-based filler of micro-nano level is uniformly dispersed in silicone oil by dispersion solvent, and mixed solution is obtained;The carbon-based filler is the mixture of one or two of carbon black and multi-walled carbon nanotube;The solvent of the mixed solution is evaporated, then inhibitor, catalyst are added until pre-crosslinking, and spinning solution is obtained;The spinning solution is added to spinning equipment, and after heating to preset spinning temperature at spinning port, spinning is formed.The application reduces the elasticity of organic silicon composite spinning solution by adding micro-nano carbon material and other rigid particles, avoids the expansion of spinning solution at spinning port, and using high spinning temperature can make organic silicon spinning solution quickly solidify and crosslink at spinning port position to inhibit the expansion of fluid at spinning port, prevent fiber from becoming thick by reducing the elasticity of spinning material outlet, so as to obtain controllable diameter organic silicon fiber without reducing sensing level.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of fiber material technology, specifically to novel organosilicon-based composite fiber materials, and more specifically, to an organosilicon flexible strain-sensing fine fiber and its preparation method. Background Technology

[0002] In recent years, with the rapid development of wearable devices, flexible skin, and human-computer interaction electronic devices, the application of flexible sensors in health monitoring, disease diagnosis, and motion detection has attracted increasing attention. Sensors can convert detected physical or chemical signals into electrical signals, playing a crucial role in signal acquisition, conversion, and transmission. Traditional rigid sensor materials are hard and brittle, which not only limits human movement but also hinders the development of sensor technology. In contrast, flexible sensors, with their excellent flexibility, deformability, and good fit to the human body, offer a more promising option for wearable devices. However, achieving excellent flexible sensing performance hinges on selecting a suitable elastic substrate material.

[0003] Among numerous materials, organosilicon stands out due to its unique comprehensive properties. This material exhibits high elasticity and excellent flexibility, allowing it to closely conform to irregular surfaces and withstand extensive deformation without easily breaking, making it ideal for meeting the needs of flexible strain sensors. Furthermore, organosilicon also possesses high-temperature resistance and chemical stability, and holds promise for improving its sensing performance and durability under extreme environmental conditions.

[0004] Currently, existing methods for preparing flexible strain sensing fibers based on organosilicon mainly focus on two aspects. The first is the template method, which relies on hollow molds, and the fiber length is only in the centimeter range, making continuous production difficult. Changing the diameter requires remaking the mold, which is cumbersome and difficult to demold, especially unfavorable for the preparation of micron-sized fibers. The second is the coating method, where the bonding force between the conductive layer and the PDMS matrix is ​​weak, and it is easy to fall off and crack after repeated stretching or friction, resulting in poor stability. Moreover, the coating thickness is difficult to control precisely.

[0005] Existing technology 1 (Han J, Wan K, Chen Z, et al. Thermospun conductive composites with a wide strain range, excellent fatigue resistance, and high linearity for fibrous strain sensors[J]. ACS Applied Engineering Materials,2023, 1(10): 2772-2781.) uses a continuous thermospinning process with a 19G spinning head, and employs KH570 modified carbon nanotubes to form a strong interface with PDMS, endowing MCPF with excellent mechanical properties. This sensor has a wide strain measurement range, can withstand 1000 tensile cycles under 50% strain conditions with good repeatability, and has excellent conductivity.

[0006] Existing technology two (Liu M, Song S, Jiang Z, et al. Sugar-plastic assisted fabrication of hollow PDMS wearable fabrics toward excellent sensory capabilities[J]. Journal of Materials Chemistry A, 2024, 12(12): 7237-7247.) uses a sugar-plastic assisted template method to prepare flexible hollow PDMS / CNT fibers, the outer layer of which is coated with a rigid conductive polydopamine-polypyrrole layer with a finger-like hierarchical structure. The fiber inner diameter is about 700 micrometers and the wall thickness is about 150 micrometers. It can provide excellent sensing performance over a wide pressure range of up to about 725 kPa and has tactile recognition capabilities based on different surface roughnesses.

[0007] Existing technology 3 (Zhang X, Xu J, Zhang X, et al. Simultaneous evaporation and foaming for batch coaxial extrusion of liquid metal / polydimethylsiloxaneporous fibrous TENG[J]. Advanced Fiber Materials, 2023, 5(6): 1949-1962.) reports a batch preparation method combining in-situ foaming and coaxial extrusion, using liquid metal as the core layer and porous PDMS as the shell layer to prepare woven triboelectric nanofibers with a diameter of 1.2 mm and a wall thickness of approximately 250-550 micrometers. Shear-thinning rheology and surface microporous structure were achieved by controlling the ink composition, and liquid metal was injected after forming hollow channels using water as a sacrificial template. The porous structure increased the effective contact area, and the open-circuit voltage and short-circuit current were increased by approximately 5 times and 7 times, respectively, compared to solid fibers. The woven fabric TENG output approximately 105 V and 1.7 µA under 3 Hz excitation, with a maximum power density of 176 mW·m. -2 It exhibits tensile strength of 150%–190% and remains stable after 2000 cycles and washing. This method can also be extended to food-grade silicone rubber and TPU matrices, demonstrating good material versatility and has been successfully applied to driving LEDs, electronic timers, and human motion monitoring.

[0008] As can be seen from the above, flexible strain sensing fibers based on silicone have shown great application potential in multiple fields. However, the fineness of traditional textile fibers is generally less than 100 micrometers, which provides properties such as flexibility during spinning and weaving. Currently reported silicone fibers, however, have diameters exceeding 500 micrometers, even reaching the millimeter level. This directly leads to a significant increase in the fiber's bending and torsional stiffness, resulting in poor flexibility. This makes it difficult for the fibers to withstand the high curvature deformations during textile processing such as twisting, knotting, and weaving, posing a serious challenge to their seamless integration into smart clothing through twisting and weaving processes. Therefore, how to maintain excellent sensing performance while effectively reducing the diameter of silicone fibers is a key breakthrough in propelling them from the laboratory to industrial mass production and commercial application. Summary of the Invention

[0009] The purpose of this invention is to address the above-mentioned shortcomings by providing a flexible strain-sensing fine fiber of silicone and its preparation method. By adding rigid particles such as micro- and nano-sized carbon materials, the elasticity of the silicone composite spinning solution is reduced, thus preventing the spinning solution from expanding at the spinneret. Using a high spinning temperature allows the silicone spinning solution to quickly solidify and cross-link at the spinneret, thereby inhibiting the expansion of the fluid at the spinneret. By reducing the outlet elasticity of the spinning material, fiber thickening is prevented, thereby obtaining silicone fibers with controllable diameter.

[0010] To achieve the above objectives, the present invention is implemented through the following technical solution: In a first aspect, the present invention provides a method for preparing organosilicon flexible strain-sensing fine fibers, comprising: Micro- and nano-sized carbon-based fillers are uniformly dispersed in silicone oil using a dispersing solvent to obtain a mixed solution; the carbon-based fillers are one or a mixture of two of carbon black and multi-walled carbon nanotubes. The solvent of the mixed solution is evaporated, and then an inhibitor and a catalyst are added until pre-crosslinking is achieved to obtain the spinning solution; The spinning solution is added to the spinning equipment, and the spinning nozzle is heated to the preset spinning temperature. The yarn is then spun and formed to obtain the desired product.

[0011] In this invention, the viscosity of the pre-crosslinked spinning solution is 20-50 Pa·s to facilitate spinning, preferably 20-30 Pa·s; the viscosity of the spinning solution can be controlled by stirring time, and can be adjusted according to the production experiment.

[0012] Furthermore, the dispersing solvent is n-hexane, n-heptane, toluene, xylene, or ethyl acetate; n-hexane is preferred. The amount of dispersing solvent has no effect on the experimental results and can be adjusted freely according to the specific experimental conditions.

[0013] Furthermore, the carbon-based filler is a mixture of carbon black and multi-walled carbon nanotubes, wherein the mass ratio of carbon black to multi-walled carbon nanotubes is (5~9):(5~1); preferably, the mass ratio is 7:3.

[0014] Furthermore, the carbon-based filler accounts for 5% to 25% of the mass of the silicone oil; preferably 10% to 15%.

[0015] Furthermore, the silicone oil comprises vinyl-terminated silicone oil and hydrogen-based silicone oil, wherein the mass ratio of the vinyl-terminated silicone oil to the hydrogen-based silicone oil is (16.95~17.2):(1~1.18).

[0016] Furthermore, the micro-nano scale mentioned in this invention refers to particle sizes in the micrometer or nanometer range; wherein the carbon black has a particle size of 15~50nm, and the multi-walled carbon nanotubes have a diameter of 5~50nm and a length of 1~50μm.

[0017] Furthermore, the carbon-based filler, dispersing solvent, and silicone oil are mixed and dispersed using a ball mill, with a ball-to-material ratio of 30:1, 20:1, 12.4:1, or 8:1, and a stirring speed of 300-600 rpm.

[0018] Furthermore, the inhibitor is ethynylcyclohexanol, propargyl alcohol, or ethynylbutanol, with a concentration of 2000~9000ppm, and the amount added is equivalent to 0.36%~1.63% of the total mass of silicone oil.

[0019] Furthermore, the catalyst is a Pt catalyst with a concentration of 2000~9000ppm, and the amount added is equivalent to 0.17~0.75% of the total mass of silicone oil. The Pt catalyst mentioned in this invention refers to a platinum coordination compound, preferably Karstedt's Catalyst (with divinyltetramethyldisiloxane as a ligand), Speier's catalyst (chloroplatinic acid dissolved in isopropanol to form a solution, the active ingredient being a complex formed by platinum atoms and hydroxyl groups), or a chloroplatinic acid isopropanol solution can be used directly.

[0020] Furthermore, the step of adding the spinning solution to the spinning equipment, heating the spinning nozzle to a preset spinning temperature, and then spinning to form the yarn includes: The spinning solution was defoamed and then injected into a syringe; Clamp the syringe containing the spinning solution onto the constant pressure injection pump and select the spinning head with the preset diameter; Adjust the temperature control equipment to bring the temperature at the spinning nozzle to the preset spinning temperature; Control the spinning solution to pass through the spinning head at a uniform speed so that it cross-links and solidifies instantly when it is extruded from the spinneret; Finally, the obtained fibers can be collected using a rotating cage.

[0021] Furthermore, the preset spinning temperature at the spinning nozzle is 150~260℃, preferably 220~255℃. Adjustable fiber diameter is achieved by controlling the spinning solution flow rate and changing the spinning needle configuration, combined with high-temperature spinning.

[0022] Secondly, the present invention also provides an organosilicon flexible strain sensing microfiber, wherein the fiber is prepared by the method for preparing organosilicon flexible strain sensing microfiber described in the first aspect.

[0023] Compared with the prior art, the beneficial effects of the present invention are as follows: The method for preparing flexible strain-sensing fine fibers of silicone described in this invention involves mixing fine-particle carbon-based filler carbon black and multi-walled carbon nanotubes into a silicone fluid. This reduces the elasticity of the silicone composite spinning solution, preventing the spinning solution from expanding at the spinneret. The carbon-based filling also improves the thermal conductivity of the matrix, thereby promoting faster and more uniform low-curing and cross-linking of the spinning solution during the spinning process. This also helps to prevent the expansion of the spun material at the outlet, thus obtaining fine fibers without reducing the sensing level. By using a high spinning temperature, the silicone spinning solution can be rapidly cured and cross-linked at the spinneret, thereby inhibiting the expansion of the fluid at the spinneret. By reducing the elasticity of the spinning material at the outlet, fiber thickening is prevented, resulting in silicone fine fibers with controllable diameter, which are more suitable for downstream weaving processes and equipment.

[0024] The organosilicon flexible strain-sensing fine fiber prepared in this invention has a minimum diameter of 73 μm. The strain sensing range of the fiber is 0–302%, with a fastest response time of 80 ms and a recovery time of 120 ms. At 200% elongation, the fiber can withstand 948 cycles of tensile strain. The tensile strength of the fiber was characterized using an INSTRON-3365 biarm material testing machine, and the tensile strength was approximately 5.69 MPa. Static high and low temperature tests showed that the fiber still exhibited stable strain response output under constant temperature environments of -30–0 °C and 50–200 °C. Even under dynamic environments, whether at high or low temperatures, the fiber maintains good sensing performance, indicating that the sensor performance is not affected by temperature changes. This provides a promising method for preparing flexible strain sensors with controllable diameter and resistance to high and low temperatures. Attached Figure Description

[0025] Figure 1 This is a schematic diagram of the spinning apparatus according to an embodiment of the present invention; Figure 2 The macroscopic morphology and diameter of the organosilicon flexible strain sensing fine fiber prepared in Example 1 are shown. Figure 3 The macroscopic morphology and diameter of the pure organosilicon fiber prepared in Comparative Example 1 are shown. Figure 4 The macroscopic morphology and diameter of the organosilicon flexible strain sensing fiber prepared in Comparative Example 2 are shown. Figure 5 The macroscopic morphology and diameter of the organosilicon flexible strain sensing fine fiber prepared in Example 2 are shown. Figure 6 The macroscopic morphology and diameter of the organosilicon flexible strain sensing fine fiber prepared in Example 3 are shown. Figure 7 The macroscopic morphology and diameter of the organosilicon flexible strain sensing fine fiber prepared in Example 4 are shown. Figure 8The macroscopic morphology and diameter of the organosilicon flexible strain sensing fine fiber prepared in Example 5 are shown. Figure 9 The images show the structural characterization of the organosilicon flexible strain sensing fine fibers prepared in Examples 1 to 5; where (a) is the FT-IR spectrum and (b) is the XRD diffraction pattern. Figure 10 The mechanical response characteristics of the organosilicon flexible strain-sensing fine fibers prepared in Examples 1 to 5 are shown in the figure; where (a) is the strain response sensitivity curve; (b) is the deformation cycle response; and (c) is the breaking strength and breaking elongation. Figure 11 The mechanical response characteristics of the organosilicon fibers prepared in Example 1, Comparative Examples 3 to 5 are shown in the figure; where (a) is the strain response sensitivity curve; (b) is the deformation cycle response; and (c) is the breaking strength and breaking elongation. Figure 12 The image shows the dynamic response characteristics of the fiber obtained in Example 1, where (a) represents the response under different deformation cycles, (b) represents the response time, and (c) represents the recovery time. Figure 13 The figure shows the long-term durability test characterization of the fiber obtained in Example 1; in the figure, (a) is the cycle durability response curve; (b) is the first 5 cycles in (a), (c) is the middle 5 cycles in (a), and (d) is the last 5 cycles in (a); Figure 14 The high-temperature strain sensing performance diagram of the fiber obtained in Example 1 is shown, where (a) is static and (b) is dynamic. Figure 15 The image shows the low-temperature strain sensing performance of the fiber obtained in Example 1, where (a) is static and (b) is dynamic. In the diagram: 1. Temperature controller; 2. Micro-injection pump; 3. Syringe; 4. Spinneret; 5. Heating jacket; 6. Fiber take-up machine; 7. Iron stand. Detailed Implementation

[0026] Preferred embodiments of the present invention will now be described in more detail with reference to the accompanying drawings and specific examples.

[0027] In the following description, certain specific details are set forth for the purpose of illustrating various disclosed embodiments in order to provide a thorough understanding of the various disclosed embodiments. However, those skilled in the art will recognize that embodiments may be practiced without one or more of these specific details. In other instances, well-known apparatuses, structures, and techniques associated with this application may not have been shown or described in detail to avoid unnecessarily obscuring the description of the embodiments.

[0028] Unless the context requires otherwise, throughout the specification and claims, the word “comprising” and its variations, such as “including” and “having”, shall be understood to have an open, inclusive meaning, that is, to be interpreted as “including, but not limited to”.

[0029] Throughout this specification, references to "an embodiment" or "an embodiment" indicate that a particular feature, structure, or characteristic described in connection with the embodiment is included in at least one embodiment. Therefore, the appearance of "in an embodiment" or "an embodiment" in various places throughout the specification does not necessarily refer to the same embodiment. Furthermore, a particular feature, structure, or characteristic may be combined in any manner in one or more embodiments.

[0030] The singular forms “a” and “the” used in this specification and the appended claims include plural references unless otherwise expressly stated herein. It should be noted that the term “or” is generally used to mean “and / or” unless otherwise expressly stated herein.

[0031] Furthermore, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0032] This invention disperses carbon black (CB) and multi-walled carbon nanotubes (MWCNTs) in hexane through vigorous mechanical stirring, then adds silicone oil to ensure uniform mixing. The mixture is then transferred to a heating stage to evaporate the solvent, and inhibitors and catalysts are added and stirred until a pre-crosslinked state is achieved. The mixture is then spun using a hot air curing method. The microstructure, chemical structure, and application performance of the resulting organosilicon flexible strain-sensing fine fibers were tested and characterized.

[0033] The raw materials used in this invention are all conventional products and can be obtained commercially. The specific preparation procedures and performance testing follow conventional techniques. The testing and analysis conducted in this invention are as follows: The mechanical properties of the prepared silicone conductive fibers were tested using an INSTRON-3365 dual-arm material testing machine. Following the national standard GB / T 14337-2022 for testing the tensile properties of short chemical fibers, the fibers were cut to 4 cm lengths and both ends were wrapped with labels. The sensors used in the tests had a range of 0–8 N, a tensile speed of 4 cm / min, and a spacing of 2 cm. To ensure greater accuracy, each fiber sample was tested an average of 20 times to obtain the average tensile strength and elongation at break.

[0034] Fourier Transform Infrared Spectroscopy (FT-IR): The obtained samples were tested using a Thermo Scientific Nicolet iS5 infrared spectrometer. For routine powder compression testing, the fiber was mixed with potassium bromide, ground in a mortar, dried using a high-temperature infrared lamp, pressed into thin sheets under 1 ton of pressure, and then placed inside the instrument. The measurement range was 400–4000 cm⁻¹. -1 The resolution is 4 cm. -1 , scanned 16 times.

[0035] Strain sensing performance testing: ① Sensing Range: The sensing range test requires two testing systems: a mechanical performance testing system and an electrical performance testing system. For the mechanical performance test, both ends of the sample are wrapped with aluminum foil. Two electrodes (representing copper foil) are connected to a Chenhua electrochemical workstation using wires. The current change during the tensile process is monitored until the sample breaks. The sample clamping distance is maintained at 20 mm, and the tensile speed is 30 mm / min.

[0036] ② Sensitivity: Sensitivity refers to the slope of the curve when the relative resistance change is plotted on the ordinate and the stretching range change on the abscissa. During mechanical property testing, aluminum foil is placed at both ends of the sample, and two electrodes (acting as copper foil) are connected to a Chenhua electrochemical workstation using wires. The resistance change of the sample during the stretching process is monitored until it breaks. The sample clamping distance is maintained at 20 mm, and the stretching speed is 30 mm / min.

[0037] ③ Durability: Stability refers to the regularity of the change in relative resistance. During mechanical property testing, aluminum foil is placed at both ends of the sample, and the two electrodes serving as aluminum foil are connected to the Chenhua electrochemical workstation with wires. The current change of the sample during the stretching process is monitored. The sample clamping distance is maintained at 20 mm, and the stretching speed is 100 mm / min. The stability of the relative resistance change is observed under 200% deformation stretching / release cycles until the fiber breaks.

[0038] ④ Response Time: The response time test involves stretching and releasing the sensor, and recording the current change using a Chenhua electrochemical workstation. The time it takes for the resistance to change from a steady state to an excited state is the response time, and the time it takes to recover from the excited state to a steady state is the recovery time.

[0039] The silicone oil raw materials used in the specific embodiments are as follows: Vinyl-terminated silicone oil: α,ω-vinyl poly(methylphenylsiloxane-dimethylsiloxane), 1000cp, vinyl content 1.0%, Guoyan Chemical New Materials Co., Ltd.; Side-bound vinyl silicone oil: α,ω-vinyl poly(methylphenylsiloxane-methylvinylsiloxane), 5000 cp, vinyl content 2.5%, Guoyan Chemical New Materials Co., Ltd.; Hydrogen-based silicone oil: α,ω-dimethyl polymethylhydrosiloxane, 80cp, hydrogen content 0.75%, Guoyan Chemical New Materials Co., Ltd.

[0040] Example 1 This embodiment provides a flexible silicone strain-sensing microfiber (CB:MWCNT ratio of 7:3), which is prepared by the following method: First, 0.28 g of CB (35 nm particle size), 0.12 g of MWCNT (30 nm diameter, 25 μm length), and 10.00 g of n-hexane were added sequentially to a ball mill jar at a ball-to-material ratio of 8:1. The mixture was stirred vigorously at 600 rpm for 2.5 h. Then, 3.78 g of vinyl-terminated silicone oil and 0.22 g of hydrogen-based silicone oil were added, and the mixture was stirred at 600 rpm for 0.5 h to ensure uniform mixing of the silicone oil and filler. The mixture was then transferred to a heating plate to evaporate the solvent. After the spinning solution cooled, 0.65% (by weight of the total silicone oil) of ethynylcyclohexanol was added dropwise to the mixed silicone oil system as an inhibitor. After stirring for 10 min, 0.5% (by weight of the total silicone oil) of Pt catalyst was added, and stirring continued for another 20 min to obtain the spinning solution.

[0041] The spinning solution is fully defoamed and then added to the spinning equipment. The spinning equipment used in this embodiment is as follows: Figure 1 As shown, the system includes a temperature controller 1, a micro-injection pump 2, a syringe 3, a spinneret 4, a heating jacket 5, a fiber take-up machine 6, and an iron stand 7. The specific steps of the spinning process are as follows: After fully degassing the above spinning solution, inject it into a 2 mL syringe 3. Clamp the syringe 3 containing the spinning solution onto the constant pressure micro-injection pump 2. The diameter of the spinning head is 0.16 mm, and the feed rate of the constant pressure micro-injection pump 2 is set to 0.40 mL / min. -1 The position of the spinneret 4 is flush with the opening of the heating jacket 5; the actual heating temperature of the heating jacket 5 is controlled by the temperature controller 1 to be about 255 ℃; when the spinning solution is extruded from the spinneret 4, the temperature rises rapidly and it quickly solidifies and cross-links. Then, it passes through the heating jacket 5 and can instantly cross-link and solidify before expansion; finally, the obtained fibers are collected by the fiber take-up machine 6.

[0042] The macroscopic morphology and diameter of the organosilicon flexible strain sensing microfiber prepared in this embodiment are as follows: Figure 2 As shown, from Figure 2 The fiber diameter is approximately 82 μm. The dynamic response characteristics of the obtained fiber are characterized as follows: Figure 12As shown in the figure, (a) represents the response under different deformation cycles, (b) represents the response time, and (c) represents the recovery time. The figure shows the stable response of the fiber under different strain ranges, with a minimum response time of 80 ms and a minimum recovery time of 120 ms. The long-term durability of the obtained fiber is characterized as follows: Figure 13 As shown in the figure, the fiber can withstand 948 strain cycles at 200% tensile strain, exhibiting excellent durability. The high-temperature strain sensing performance of the obtained fiber is as follows: Figure 14 As shown in the figure, (a) represents static conditions and (b) represents dynamic conditions. It can be seen from the figure that the fiber maintains good sensing performance even under high-temperature conditions, exhibiting excellent temperature stability. The low-temperature strain sensing performance of the obtained fiber is as follows: Figure 15 As shown in the figure, (a) represents static and (b) represents dynamic. It can be seen from the figure that the fiber can maintain stable sensing performance even in low temperature environments.

[0043] Comparative Example 1 This comparative example provides a pure organosilicon fiber, the preparation method of which is as follows: 3.78 g of vinyl-terminated silicone oil and 0.22 g of hydrogen-based silicone oil were added sequentially to a ball mill jar, and the mixture was stirred at 600 rpm for 10 min to ensure homogeneity. 150 ppm of the inhibitor acetylenecyclopropanol was added to the mixed ternary silicone oil system, and after stirring for 5 min, 30 ppm of Pt catalyst was added, followed by stirring for another 4 min. The remaining preparation method was the same as in Example 1.

[0044] The macroscopic morphology and diameter of pure organosilicon fibers prepared without carbon materials in this comparative example are as follows: Figure 3 As shown, from Figure 3 It can be seen that the fiber diameter is 0.190mm (i.e. 190μm). Since no carbon material is added, the pure organic silicon fiber is colorless and transparent.

[0045] Comparative Example 2 This comparative example provides an organosilicon flexible strain sensing fiber, the amount of each component is the same as in Example 1, except that the actual heating temperature for spinning is 150°C, the other preparation steps and parameters are the same as in Example 1.

[0046] The macroscopic morphology and diameter of the pure organosilicon fibers prepared in this comparative example are as follows: Figure 4 As shown, from Figure 4 It can be determined that the fiber diameter is 173 μm.

[0047] Example 2 This embodiment provides an organosilicon flexible strain sensing microfiber (CB:MWCNT ratio of 5:5). In its preparation method, except that the amount of CB is 0.20g and the amount of MWCNT is 0.20g, the amounts of other components, preparation steps and parameters are the same as in Example 1.

[0048] The macroscopic morphology and diameter of the organosilicon flexible strain sensing microfiber prepared in this embodiment are as follows: Figure 5 As shown, from Figure 5 It is known that the fiber diameter is approximately 99 μm.

[0049] Example 3 This embodiment provides a flexible strain-sensing microfiber of silicone (CB:MWCNT ratio of 6:4). In its preparation method, except that the amount of CB is 0.24g and the amount of MWCNT is 0.16g, the amount of other components, preparation steps and parameters are the same as in Example 1.

[0050] The macroscopic morphology and diameter of the organosilicon flexible strain sensing microfiber prepared in this embodiment are as follows: Figure 6 As shown, from Figure 6 It is known that the fiber diameter is approximately 94 μm.

[0051] Example 4 This embodiment provides a flexible strain-sensing microfiber of silicone (CB:MWCNT ratio of 8:2). In its preparation method, except that the amount of CB is 0.32g and the amount of MWCNT is 0.08g, the amount of other components, preparation steps and parameters are the same as in Example 1.

[0052] The macroscopic morphology and diameter of the organosilicon flexible strain sensing microfiber prepared in this embodiment are as follows: Figure 7 As shown, from Figure 7 It is known that the fiber diameter is approximately 85 μm.

[0053] Example 5 This embodiment provides a flexible strain-sensing microfiber of silicone (CB:MWCNT ratio of 9:1). In its preparation method, except that the amount of CB is 0.36g and the amount of MWCNT is 0.04g, the amount of other components, preparation steps and parameters are the same as in Example 1.

[0054] The macroscopic morphology and diameter of the organosilicon flexible strain sensing microfiber prepared in this embodiment are as follows: Figure 8 As shown, from Figure 8 It is known that the fiber diameter is approximately 73 μm.

[0055] Figure 9 The figures show the structural characterization of the organosilicon flexible strain sensing microfibers prepared in Examples 1 to 5; where (a) is the FT-IR spectrum and (b) is the XRD diffraction pattern; from figure (a), it can be seen that the organosilicon flexible strain sensing microfibers with different proportions of carbon-based filler can achieve different wavelengths at 1097.3 cm⁻¹. -1 and 1020.2 cm -1 The peak is the Si-O-Si stretching vibration peak; at 432.0 cm⁻¹.-1 The peak represents the C=C stretching vibration of the phenyl group in the fiber molecular chain; at 1261.2 cm⁻¹. -1 The peak represents the stretching vibration of Si-CH3; at 2964.1 cm⁻¹. -1 The sharp peak appearing at 1412.4 cm⁻¹ represents the stretching vibration of -CH in the vinyl group; -1 The absence of the characteristic peak of Si-CH=CH2 observed nearby confirms the successful preparation of the organosilicon fiber. XRD analysis in Figure (b) shows that after adding 10% (by total mass) of MWCNT / CB composite filler to the silicone oil, the diffraction peak of PMPS at 2θ=22° shifted slightly to 21.89°. This change is attributed to the embedding of CB spherical particles into the interlayer gaps of the PMPS molecular chains, producing a physical isolation effect that leads to a slight increase in interchain spacing. This also indirectly proves the successful embedding of carbon black and multi-walled carbon nanotubes.

[0056] Figure 10 The figures show the mechanical response characteristics of the organosilicon flexible strain sensing fine fibers prepared in Examples 1 to 5; where (a) is the strain response sensitivity curve; (b) is the deformation cycle response; and (c) is the breaking strength and breaking elongation. It can be seen from the figures that the fibers have a wide strain sensing range under different filler ratios, and the breaking strength of the fibers is higher than 5.69 MPa. Figure 10 It is known that the fiber has the best strain sensing ability and mechanical properties when the filler ratio is 7:3, therefore the filler ratio of 7:3 is preferred.

[0057] Comparative Example 3 (5% addition of side vinyl silicone oil) This comparative example provides an organosilicon sensing fiber. In its preparation method, except for the amount of terminal vinyl silicone oil (3.60 g), side vinyl silicone oil (0.18 g), and hydrogen-based silicone oil (0.22 g), the amounts of other components, preparation steps, and parameters are the same as in Example 1. The obtained organosilicon sensing fiber has a sensing range of 0–274.9% and a breaking strength of approximately 7.59 MPa.

[0058] Comparative Example 4 (10% addition of side vinyl silicone oil) This comparative example provides an organosilicon sensing fiber. In its preparation method, except for the amount of terminal vinyl silicone oil (3.40 g), side vinyl silicone oil (0.34 g), and hydrogen-based silicone oil (0.26 g), the amounts of other components, preparation steps, and parameters are the same as in Example 1. The obtained organosilicon sensing fiber has a sensing range of 0–219.4% and a breaking strength of approximately 7.37 MPa.

[0059] Comparative Example 5 (15% addition of side vinyl silicone oil) This comparative example provides an organosilicon sensing fiber. In its preparation method, except for the amount of terminal vinyl silicone oil (3.25 g), side vinyl silicone oil (0.48 g), and hydrogen-based silicone oil (0.26 g), the amounts of other components, preparation steps, and parameters are the same as in Example 1. The obtained organosilicon sensing fiber has a sensing range of 0–201.0% and a breaking strength of approximately 7.93 MPa.

[0060] Figure 11 The mechanical response characteristics of silicone fibers prepared by the method with different amounts of polyvinylphenyl silicone oil added to the ends of Examples 1, 3, and 5 are shown in the figure; where (a) is the strain response sensitivity curve; (b) is the deformation cycle response; and (c) is the breaking strength and elongation at break. Figure 11 It is known that the fiber has the greatest strain sensing performance when no side vinyl silicone oil is added, therefore it is preferred to not add side vinyl silicone oil.

[0061] The various embodiments of the present invention have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and principles of the described embodiments, and these modifications and variations should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing organosilicon flexible strain-sensing fine fibers, characterized in that, include: Micro- and nano-sized carbon-based fillers are uniformly dispersed in silicone oil using a dispersing solvent to obtain a mixed solution; the carbon-based fillers are one or a mixture of two of carbon black and multi-walled carbon nanotubes. The solvent of the mixed solution is evaporated, and then an inhibitor and a catalyst are added until pre-crosslinking is achieved to obtain the spinning solution; The spinning solution is added to the spinning equipment, and the spinning nozzle is heated to the preset spinning temperature before spinning and forming to obtain the desired product.

2. The method for preparing organosilicon flexible strain-sensing fine fibers according to claim 1, characterized in that, The dispersing solvent is n-hexane, n-heptane, toluene, xylene, or ethyl acetate.

3. The method for preparing organosilicon flexible strain-sensing fine fibers according to claim 1, characterized in that, The carbon-based filler is a mixture of carbon black and multi-walled carbon nanotubes, wherein the mass ratio of carbon black to multi-walled carbon nanotubes is (5~9):(5~1). And / or, the carbon-based filler accounts for 5% to 25% of the mass of the silicone oil.

4. The method for preparing organosilicon flexible strain-sensing fine fibers according to claim 1, characterized in that, The silicone oil includes vinyl-terminated silicone oil and hydrogen-based silicone oil, and the mass ratio of the vinyl-terminated silicone oil to the hydrogen-based silicone oil is (16.95~17.2):(1~1.18).

5. The method for preparing organosilicon flexible strain-sensing fine fibers according to claim 1, characterized in that, The carbon black has a particle size of 15-50 nm, and the multi-walled carbon nanotubes have a diameter of 5-50 nm and a length of 1-50 μm.

6. The method for preparing organosilicon flexible strain-sensing fine fibers according to claim 1, characterized in that, The carbon-based filler, dispersing solvent, and silicone oil are mixed and dispersed using a ball mill with a ball-to-material ratio of 30:1, 20:1, 12.4:1, or 8:1 and a stirring speed of 300-600 rpm.

7. The method for preparing organosilicon flexible strain-sensing fine fibers according to claim 1, characterized in that, The inhibitor is ethynylcyclohexanol, propargyl alcohol, or ethynylbutanol, with a concentration of 2000~9000ppm, and the amount added is equivalent to 0.36%~1.63% of the total mass of silicone oil; And / or, the catalyst is a Pt catalyst with a concentration of 2000~9000ppm, and the amount added is equivalent to 0.17~0.75% of the total mass of silicone oil.

8. The method for preparing organosilicon flexible strain-sensing fine fibers according to claim 1, characterized in that, The step of adding the spinning solution to the spinning equipment, heating the spinning nozzle to a preset spinning temperature, and then spinning to form the yarn includes: The spinning solution was defoamed and then injected into a syringe; Clamp the syringe containing the spinning solution onto the constant pressure injection pump and select the spinning head with the preset diameter; Adjust the temperature control equipment to bring the temperature at the spinning nozzle to the preset spinning temperature; The spinning solution is controlled to pass through the spinning head at a uniform speed so that it is instantly cross-linked and solidified when it is extruded from the spinneret.

9. The method for preparing organosilicon flexible strain-sensing fine fibers according to claim 1, characterized in that, The preset spinning temperature at the spinning nozzle is 150~260℃.

10. A flexible strain-sensing microfiber made of organosilicon, characterized in that, The fiber is prepared by the method for preparing organosilicon flexible strain sensing fine fiber according to any one of claims 1 to 9.